Integrating hydrogen-powered fuel cell electric buses into grid-forming microgrids: A solution for emergency energy needs - Bayrak, Gokay; Basaran, Kivanc; Lazaroiu, Alexandra Catalina (Pergamon-Elsevier Science Ltd, 2025)
Fuel cell electric (FCE) buses have high-capacity batteries reaching up to 250-300 kW and high energy densities with hydrogen, so they can be used as a Mobile Microgrid (MoMG) by being supported by renewables. In this study, an FCE bus comprising a SOFC fuel cell stack and a battery is modeled as a Mobile Microgrid (MoMG) using MATLAB/Simulink to deliver mobile electrical energy support to regions inaccessible during disaster situations. To develop the V2L, V2V, and V2G functions of the MoMG, an Enhanced Grid Forming Control (EGFC) method is proposed, considering the IEEE 2800-2022 standards to ensure inverter-grid synchronization. In the proposed model, sudden changes in hydrogen power, evaluation of battery energy storage system (BESS) response during sudden load change, islanding conditions, and temporary and permanent faults are investigated. EGFC enables the FCE bus to maintain operation under both steady-state and transient conditions, achieving +1.5 % in grid voltage and current, +3 % grid active power and reactive power, and +0.01 Hz in frequency. The obtained results show that the proposed EGFC provides a reliable and stable grid integration of an FCE bus, providing the MoMG with low-voltage ride-through (LVRT) and fault ride-through (FRT) capabilities.
Keywords: Hydrogen; Fuel cell electric bus; Mobile microgrid; Solid oxide fuel cells (SOFC); Grid forming control; V2G